LIVE Course for free

Rated by 1 million+ students
Get app now
0 votes
19 views
in Quadratic Equations by (54.3k points)
closed by
If m - 3n = 2 and m2- 4mn + 3n2 − 24  = 0, then what is (m + 2n) equal to
1. 12
2. 27
3. 17
4. 10
5. None of these

1 Answer

0 votes
by (30.0k points)
selected by
 
Best answer
Correct Answer - Option 2 : 27

Calculation:

Here, m2- 4mn + 3n2 − 24 = 0

\(\rm ⇒m^2-4mn+(2n)^2-n^2-24=0\)

\(\rm ⇒(m-2n)^2=24+n^2\)

We have, m - 3n = 2 ⇒ m = 3n + 2

\(⇒\rm (3n +2-2n)^2=24+n^2 \)

\(\\⇒ (n+2)^2=24+n^2\)

\(⇒ n^2+4n+4=24+n^2\)

\(\rm ⇒4n=20\)

⇒ n = 5

Putting, value of n in m - 3n = 2, we get 

m = 2 + 3(5) = 2 + 15 = 17

∴ (m + 2n) = 17 + 2(5)

= 17 + 10

= 27

Hence, option (3) is correct. 

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

...